School fears of younger teenagers during the Covid-19 pandemic - Semina I. V. (Technopark of universal pedagogical competencies, 2023)
This work is aimed at studying the features of the manifestation of learning fears in boys and girls of early adolescence during school time during normal times and during the transition to distance learning in connection with the COVID-19 pandemic. The results of the study showed the presence of specific learning fears during the pandemic, as well as the relationship between the personality type of younger adolescents (masculine, feminine and androgynous) and learning fears such as “experiencing social stress”, “fear of a situation of knowledge testing”, “fear of not meeting expectations of others”, as well as “problems and fears in relationships with teachers”, “general school anxiety” and “low physiological resistance to stress”.
Keywords: младший подростковый возраст; школьная тревожность; pandemic; пандемия; COVID-19; COVID-19; school anxiety; учебные страхи; гендерный тип личности; junior adolescence; school fears; gender personality type